COSSACK ETHOS – A DOMINANT OF UKRAINIAN SPIRITUAL CULTURE - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the study of the role of Cossack ethos in the development of Ukrainian spiritual culture of XVII-XIX centuries.